Prosperity preaching in West Africa: An evaluation of a contemporary ideology from a New Testament perspective - Kahl, Werner (Ghana Bulletin of Theology, 2007)
Prosperity preaching is a powerful trend in Pentecostalism, and it is also an issue in West Africa. In this article, the author critically examines the way prosperity preachers interpret the New Testament. According to his understanding prosperity preaching tend to (mis-)use the Biblical evidence for purposes contrary to the meaning of the Gospel in the New Testament. However, their insistence that the Gospel affects every aspect of life is to be taken seriously. From the New Testament witnesses to the Gospel, the author suggests a model of caring for the needs of others in community as an alternative to a self-centred endorsement of a Western materialistic value system.
free